2009
DOI: 10.1016/j.pbb.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and cocaine combined effect on cocaine-induced changes in HPA and HPG axes hormones in men

Abstract: Nalbuphine, a mixed mu-/kappa-opioid analgesic, may have potential as a new medication for the treatment of cocaine abuse. Kappa-opioid agonists functionally antagonize some abuse-related and locomotor effects of cocaine, and both kappa-selective and mixed mu-/kappa-opioids reduce cocaine self-administration by rhesus monkeys. Because cocaine's interactions with the hypothalamicpituitary-adrenal and (HPA) hypothalamic-pituitary-gonadal (HPG) axes may contribute to its reinforcing properties, we examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 180 publications
(195 reference statements)
1
9
0
Order By: Relevance
“…) and disrupts pituitary–adrenal axis function increasing plasma cortisol levels (Goletiani et al . ). The increase in plasma PRL levels agreed with the increase in PRL levels found in rhesus monkeys after chronic cocaine administration (Mello et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and disrupts pituitary–adrenal axis function increasing plasma cortisol levels (Goletiani et al . ). The increase in plasma PRL levels agreed with the increase in PRL levels found in rhesus monkeys after chronic cocaine administration (Mello et al .…”
Section: Discussionmentioning
confidence: 97%
“…Increase in LH, adrenocorticotropin hormone (ACTH), and cortisol, decrease in prolactin e unchanged testosterone levels have been found in men after intravenous low-dose cocaine injection (0.2-0.4 mg/kg) [93,94]. Conversely, in men who chronically use cocaine, lower free testosterone concentrations have been found, while gonadotropins did not differ compared to nonusers [95].…”
Section: Effects On Testosterone Productionmentioning
confidence: 99%
“…Acute i.v. doses of the κ-receptor agonist/µreceptor antagonist nalbuphine (5 mg/70 kg) slightly reduce the reinforcing effects of cocaine and significantly decrease diastolic blood pressure in current cocaine abusers [53]. The neuroendocrine alterations produced by cocaine administration to current cocaine abusers on luteinizing hormone, cortisol, and adrenocorticotropic hormone are attenuated by acute i.v.…”
Section: Studies In Humansmentioning
confidence: 99%
“…In monkeys, κ agonists reduce cocaine intake [19, 26, 33-35, 40, 48]. Although some studies reported that chronic administration of κ agonists increased the motor performance and the dopamine overflow produced by cocaine [21,37], most studies of acute and chronic administration of κ-opiod receptor agonists suggest that these compounds have antiaddictive effects [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Endogenous κ-Opioid Systems Modulate the Effects Of Psychostmentioning
confidence: 99%
See 1 more Smart Citation